Characterization of heterogeneity and nonlinearity in material properties of nuclear graphite using an inverse method - Lin, L; Li, H; Fok, A; Joyce, M; Marrow, J (2008)
A finite-element-based inverse method has been developed to allow the characterization of the heterogeneity and nonlinearity in material properties of isotropic nuclear graphite using a single experimental test. The method is implemented into the commercial finite element code ABAQUS using its User Material (UMAT) Subroutine for ease of application. The program has been verified using simulated examples with idealized distributions of elastic modulus and the results showed rapid convergence with good accuracy. Finally, the method was applied to actual mechanical testing of nuclear graphite for which the heterogeneous distribution and nonlinearity of material properties were evaluated. © 2008.